Pengaruh Metode Inkuiri Termbimbing terhadap Pemahaman Konsep Siswa Kelas V SD pada Mata Pelajaran IPAS - Foza, Neila; Bahri, Samsul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
Conceptual understanding is a fundamental aspect of science and social studies (IPAS) learning, as it serves as the foundation for students to relate scientific and social knowledge to phenomena encountered in everyday life. A strong conceptual understanding enables students not only to recall information but also to explain, classify, and appropriately apply concepts in various IPAS learning contexts. This study aimed to examine whether the guided inquiry method has an effect on students’ conceptual understanding in the IPAS subject among fifth-grade students at SDN 1 Syamtalira Bayu. The research employed a quantitative approach using a quasi experimental design. The research population consisted of 54 fifth-grade students from two classes. Purposive sampling was used to select the sample, comprising 27 students from class Vb as the experimental group and 27 students from class Va as the control group. Data were collected using a pretest and posttest consisting of 10 multiple choice questions. The collected data were analyzed using an Independent Samples t-test with the assistance of SPSS version 21. Based on the data analysis, the significance value obtained was 0.023, which was less than 0.05; therefore, H₀ was rejected and Hₐ was accepted. It can be concluded that the guided inquiry method has a significant effect on students’ conceptual understanding in the IPAS subject among fifth-grade students at SDN 1 Syamtalira Bayu. These findings indicate that the implementation of the guided inquiry method positively influences students’ conceptual understanding in solving problems related to IPAS learning